Single versus combined immunoregulatory approachusing PD-1 and CTLA-4 modulators in controlling sepsis - Rudick, Courtney P. (Expert Rev Clin Immunol, 2017)
INTRODUCTION: Sepsis is a disease process characterized by an extreme inflammatory response followed by a period of severe immunosuppression. In recent years, there has been improved survival in the initialimmune response during systemic inflammatory response syndrome, and compensatory anti-inflammatory response, yet is mostly unchanged with 18–30% mortality during the laterstage of sepsis despite numerous Phase 3 clinical trials. AREAS COVERED: This review article presents a critical evaluation of the most promising newer studies aimed at improving the immunosuppressive stage of sepsis. Administration of DHEA/AED/AET show promise in improving survival. Blockade of signaling pathways for PD-1/PD-L1/CTLA-4, and partial blockade of TREM-1 signaling, and modification to sTREM-1 and the JAK/STAT pathway are promising methods of restoring host immune response and improving survival. While there has been significant progress, currently no findings have been translated into effective clinical interventions. EXPERT COMMENTARY: Clinical success by immunomodulation with individual immune mediator is encouraging and should progress to evaluating combined methods of immunoregulation. Since most of the animal studies do not reproduce human sepsis, development of better animal models and moving toward human studies for intervention will lead to the most beneficial findings in translational science.